Individuality and relationality in Spinoza - Merçon, Juliana (Revista Conatus - Filosofia de Spinoza (ISSN 1981-7509), 2008)
Spinoza foi um dos primeiros filósofos modernos a definir o indivíduo não como um sistema fechado, mas como uma pluralidade unificada mantida por suas trocas com o ambiente. O foco de Spinoza na relacionalidade dos indivíduos tem permitido variadas interpretações de sua teoria da individuação. O propósito deste artigo é discutir algumas destas distintas interpretações e demonstrar como sua ontologia é mais claramente compreendida quando investigada em associação com sua epistemologia. Abstract Spinoza was one of the first modern philosophers to define the individual not as a closed system, but as a unified plurality sustained by its exchanges with the environment. Spinoza’s focus on the relationality of individuals has allowed various interpretations of his theory of individuation. The purpose of my paper is to discuss some of these distinct interpretations and to demonstrate how his ontology is illuminated when investigated in close association with his epistemology. Keywords: Individuality. Relationality. Adequate expansion. Transindividuality.